Rapid fabrication of nanoporous iron by atmospheric plasma for efficient wastewater treatment. (2nd July 2023) - Lu, AnKang; Li, HanYu; Yu, Yao; Liu, Lin
Abstract: Nanoporous (NP) iron with large surface area is highly desired for wastewater degradation catalysis. However, it remains a challenge for the fabrication of NP-Fe because the conventional aqueous dealloying or liquid metal dealloying are not applicable. Herein, a novel and universal plasma-assisted electro-dealloying technique was utilized to fabricate NP-Fe. The NP-Fe demonstrates evenly distributed pore structure. The pore density can be tuned by the variation of the ratio of Fe and Zn in the precursor, and the average pore size can be tuned by the processing time. Owing to its large specific surface area, the NP-Fe shows excellent wastewater degradation performance, which is 26 times better than that of commercial zero-valent iron catalysts. This study provides a useful approach to fabricate NP active metals with enhanced catalytic performance.